2022
DOI: 10.1007/s12020-022-03247-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, biochemical features and functional outcome of patients with SARS-CoV-2-related subacute thyroiditis: a review

Abstract: Introduction SARS CoV-2 infection involves many organs and systems, including the thyroid, in which it manifests itself as subacute thyroiditis (SAT). After our first description of SAT due to SARS-CoV2 infection, other reports have confirmed the correlation between SARS-CoV-2 and SAT. We review the cases of SAT associated with COVID-19 to highlight its peculiar clinical and biochemical features, including its outcome and what it has added to our understanding of SAT. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 45 publications
6
14
1
Order By: Relevance
“…Consistent with early reviews (4,11,(64)(65)(66), we observed at least one of the ESR or CRP variables elevating in all patients. The ESR increased in the majority of the cases (99%), while the CRP increased in 85%.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with early reviews (4,11,(64)(65)(66), we observed at least one of the ESR or CRP variables elevating in all patients. The ESR increased in the majority of the cases (99%), while the CRP increased in 85%.…”
Section: Discussionsupporting
confidence: 92%
“…The clinical SAT symptoms might not be typical; thus, thyroid ultrasonography may help to get to the correct diagnosis. In this regard and in agreement with almost all the previous cases ( 4 , 11 , 64 66 ), 92 patients in this review had the classic sonographic findings of SAT, which include bilateral or unilateral, localized or multifocal, and poorly defined hypoechoic regions ( 72 ). The previously conducted studies also found that in order to assess thyroid function, radionuclide scanning combined with ultrasound examination could significantly increase the diagnostic rate of SAT.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations